Impact of Arteriovenous fistula creation on estimated glomerular filtration rate decline in Predialysis patients - Bénard, Valérie (BMC Nephrol, 2019)
BACKGROUND: Arteriovenous fistula (AVF) is the vascular access of choice for patients on hemodialysis. Recent evidence suggests that AVF creation may slow estimated glomerular filtration rate (eGFR) decline. The study objective was to assess the impact of the AVF creation on eGFR decline, after controlling for key confounding factors. METHODS: This retrospective cohort study included adult patients followed in a single-center predialysis clinic between 1999 and 2016. Patients with a patent AVF were followed up to 2 years pre- and post-AVF creation. Estimated GFR trajectory was reported using linear mixed models adjusted for demographic characteristics, comorbidities and use of renin-angiotensin-aldosterone blockade. RESULTS: A total of 146 patients were studied with a median age 68.7 (60.5–75.4) years and a median eGFR at time of AVF creation of 12.8 (11.3–13.9) mL/min/1.73m(2). The crude annual eGFR decline rates were − 3.60 ± 4.00 mL/min/1.73 m(2) pre- and − 2.28 ± 3.56 mL/min/1.73 m(2) post-AVF, resulting in a mean difference of 1.28 mL/min/1.73 m(2) (95% CI 0.49, 2.07). In a mixed effect linear regression model, monthly eGFR decline was − 0.63 (95% CI -0.81, − 0.46; p <  0.001) mL/min/1.73m(2)/month. The period after AVF creation was associated with a relatively higher eGFR (β 0.94, 95% CI 0.61–1.26, p <  0.001). There was a significant association between follow-up time and the period pre/post AVF (β 0.19, 95% CI 0.16, 0.22; p <  0.001) such that eGFR decline was more attenuated each month after AVF creation. CONCLUSIONS: In this cohort, AVF creation was associated with a significant reduction of eGFR decline. Further prospective studies are needed to confirm this association.